Human Resource Management (HRM) and Information Technology (IT): Some Empirical Evidences in the Context of Saudi Arabia - Mat, Razali Bin (Journal of Education and Vocational Research, 2012)
This research is intended to examine the relationships among the use of IT by organizations, HRM performances on its functional tasks on productivity, efficiency, and cost-effectiveness, organizational performances, the IT implementation gap, HRM transformation gap, and organizational performances gap. The HRM practitioners who are registered as members of Arabian Society of Human Resource Management (ASHRM) were randomly selected as respondents to response to the questions in the questionnaire. All the four hypotheses were statistically supported. The use of IT had significant correlations with the HRM functional performances based on productivity, efficiency, and cost-effectiveness. In addition, the IT implementation gap proved to be significant to the overall performances of HRM functional task. Several practical implications from the research findings and future research agenda were discussed at the end of the report.